Linkages of Various Calcium Sources on Immune Performance, Diarrhea Rate, Intestinal Barrier, and Post-gut Microbial Structure and Function in Piglets - Wang, Kaijun; Yang, Anqi; Peng, Xiaomin; Lv, Feifei; Wang, Ying; Cui, Yao; Wang, Yuhan; Zhou, Jianqun; Si, Hongbin (Frontiers in Nutrition, 2022)
The purpose of this experiment was to investigate the effects of different sources of calcium on immune performance, diarrhea rate, intestinal barrier, and post-intestinal flora structure and function in weaned piglets. A total of 1,000 weaned piglets were randomly assigned to five groups 10 replicate pens per treatment, 20 piglets per pen and fed calcium carbonate, calcium citrate, multiple calcium, and organic trace minerals of different concentrations of acidifier diets. The results of the study showed that the replacement of calcium carbonate with calcium citrate and multiple calcium had almost no significant effect on immune indexes (IL-1β, IL-6, IL-10, TNF-α) of piglets compared with the control group (p > 0.05). The five groups did not show a change in the diarrhea rate and diarrhea index (p > 0.05). The diet containing multiple calcium dramatically decreased the TP compared to the C and L diet (p < 0.05). No significant difference in HDL was noted in the five groups (p > 0.05). However, the concentration of LDL in blood in the multiple calcium group was significantly higher than that in groups L and D (p < 0.05). Moreover, the concentration of Glu in blood in the multiple calcium group was significantly higher than that in group C (p < 0.05). Compared with the control group, calcium citrate plus organic trace minerals diet markedly increased UCG-005 abundance in the colon (p < 0.05). In addition, the relative abundance of Prevotellaceae_NK3B31_group had an upward trend in the colon of the M group compared to the D group (p = 0.070). Meanwhile, calcium citrate plus organic trace minerals diet markedly increased Clostridium_sensu_stricto_1 abundance in the colon (p < 0.05). Metagenomic predictions by PICRUSt suggested that the colonic and fecal microbiota was mainly involved in carbohydrate metabolism, amino acid metabolism, energy metabolism, and metabolism of cofactors and vitamins.